Interval non-probabilistic reliability of surrounding jointed rockmass considering microseismic loads in mining tunnels. (November 2018) - Dong, Longjun; Sun, Daoyuan; Li, Xibing; Ma, Ju; Zhang, Lingyun; Tong, Xiaojie
Abstract: The frequent microseismicity affects the stability and reliability of surrounding rock and the safety of supporting structures in deep mining tunnels. The limit state equations of rock blocks under microseismic loads were developed to indicate the stability conditions and sliding characteristics. The scarce field data result in the uncertainty of the physico-mechanical parameters of tunnel surrounding rock. According to the insufficient statistical information for the rockmass, a method of the interval non-probabilistic reliability was proposed to analyze the stability of surrounding jointed rockmass. The method considered both microseismic loads and the uncertainty of rockmass parameters. The solving approach of interval non-probabilistic reliability was optimized, and it can be available when the field data is scarce. To verify the proposed method, the interval non-probabilistic reliability was used to evaluate the stability of the mining tunnel rockmass in the Yongshaba mine (China). The calculated interval non-probabilistic reliability was compared with the safety factor and random reliability. Results show that the interval non-probabilistic reliability model is in agreement with practical situations. It is proved that the proposed method of interval non-probabilistic reliability, considering both the uncertainty of the rockmass parameters and the microseismic loads, is a beneficial complement to the traditional analysis methods of safety factor and random reliability.